Investigating the benefits of online peer mentoring for student confidence and motivation. Issue 4 (15th November 2018) - Fayram, Jo; Boswood, Nel; Kan, Qian; Motzo, Anna; Proudfoot, Anna
Abstract : Purpose: The purpose of this paper is to report the findings of an online peer-mentoring initiative for language students at the Open University, UK. The communities of practice (CoP) model (Wenger, 2010) was used as a theoretical framework within which to explore the nature and extent of mentor and mentee participation; and the impact of the scheme on student confidence and motivation. Design/methodology/approach: Within a qualitative paradigm, multi-data sources were employed to collect and analyse data. Participation was measured from analysis of online interaction, while participant views were captured through interviews, forum posts and surveys. Findings: Findings revealed that mentors were perceived by students who used the scheme to be instrumental in building confidence and motivation. In addition, varying participation patterns indicated that students used the online learning communities to meet their differing needs during their studies. These needs involved passively reading posts as well as actively posting. Research limitations/implications: Any direct statistical correlation between student confidence and motivation and online peer mentoring was beyond the scope of this study and could be the focus of future research. Additionally, research might also explore the impact of student mentors on student participation in wider CoPs. Practical implications: Practical recommendations from the study include the importance of mentor training to develop effective communication strategies and to differentiate the role from that of tutor moderators, whose remit is to respond to academic content-related queries in module-wide forums. Originality/value: There is little research into the nature and impact of online peer mentoring on student motivation and confidence. This study aimed to bridge this gap.